Innovative teaching and technology in the service of science: Recruiting the next generation of STEM students - Thomas McNally (Journal of the Scholarship of Teaching and Learning, 2012)
This article examines innovative approaches to augmenting science lessons taught in middle and high school, with special emphasis on theimportance of the early teen years, when experiences both in and out of school have significant impact on career decisions. This is a reflective essay on the recent work of science educators and educational researchers hoping to increase science literacy in American students and inspire them to choose STEM careers. The creativity and breadth of the techniques discussed have important implications for the way in which student teachers are prepared within college secondary education programs.